Designing Board Games to Educate Female Sex Workers on Sexually Transmitted Infection Using The ADDIE Model - Kartika, Ria Chandra; Setyowati, Lisus; Hikmah, Faiqatul; Satya, Malinda Capri Nurul; Yuana, Dia Bitari Mei; Khamid, M. Nur (International Journal of Healthcare and Information Technology, 2025)
Infectious disorders known as sexually transmitted infections (STIs) are spread through sexual contact. Female sex workers (FSWs) are particularly vulnerable to STIs. As of right now, FSWs' STI prevention practices are still insufficient. This is brought on by ignorance of STIs and failure to use condoms during sexual activity. This study's goal is to use the ADDIE Model to create a board game that educates female sex workers about sexually transmitted infections; Methods:  This research employed a research and development (R&D) approach utilizing the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. In the analysis stage, needs assessment was conducted to determine gaps in existing STI health promotion efforts. In the design stage, a board game concept was created tailored to FSW characteristics. During development, the board game was produced and subjected to feasibility testing for both media and content. The implementation stage involved a media trial with selected participants, and the evaluation stage focused on assessing the practicality and effectiveness of the game; Results: The analysis showed that FSWs had limited knowledge of STIs, and existing health promotion methods were not sufficiently interactive or engaging. The developed board game achieved a media feasibility score of 92% and a content feasibility score of 85%, indicating high practicality without the need for major revisions. During the implementation phase, 15 FSWs participated in a trial, with 93% reporting the game was practical and engaging; Conclusions: The conclusion of this study is that using board games as a health promotion medium is very feasible for FSW to increase their knowledge about STIs because they are more interactive, enjoyable, new, and the information is relevant to what FSWs need to know.